„Balladyna”, czyli o próbie karnawalizacji literatury romantycznej - Kurska, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article presents Juliusz Słowacki’s attempts to free Balladyna from the pathos of the patriotic form. The poet achieves this by exploiting and confronting diverse strategies: Shakespearean and Ariostan irony as well as the carnivalization poetics. Not only do they allow Słowacki to expand his artistic freedom, but the drama also breaks free of the cultural shackles of pathos and solemnity. Moreover, these strategies make the drama more appealing owing to laughter which violates the ‘sacred’ status of a Romantic work. In Balladyna, Słowacki offers a carnivalistic formula of ‘play-literature’, challenging the stereotypical notions and expectations of the readership and striving to revolutionize native art. By means of irony and laughter, the poet distances himself from the ideas of Polish Romanticism, creating a new model of a literary work that aesthetically goes beyond the 19th century.